Retrospective and comparative study of inflammatory myofibroblastic tumor of the liver. Issue 5 (May 2015) - Yang, Xiaobo; Miao, Ruoyu; Yang, Huayu; Chi, Tianyi; Jiang, Chao; Wan, Xueshuai; Xu, Yiyao; Xu, Haifeng; Du, Shunda; Lu, Xin; Mao, Yilei; Zhong, Shouxian; et al.
Abstract Background and Aim Inflammatory myofibroblastic tumor of the liver (IMTL) is a very rare benign disease with a good prognosis. The study aims to determine the clinical, radiological, and pathological characteristics of IMTL. The diagnosis and treatment strategies were discussed. Methods A total of 11 patients with pathologically confirmed IMTL receiving treatment over a 15‐year period were reviewed retrospectively. The analysis included demographics information and pertinent clinical data. Results obtained from patients with hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (IHCC), and metastatic liver cancer (MLC) receiving surgical resection were compared. Results In comparison to HCC, IHCC, and MLC, IMTL has an earlier onset (P < 0.001). IMTL patients had significantly lower aspartate aminotransferase (P = 0.003) and higher alkaline phosphatase (P = 0.034) than HCC patients, and higher gamma‐glutamyl transpeptidase (P = 0.010) than MLC patients. Increased serum α‐fetoprotein level was detected in only one patient. Serum α‐fetoprotein was significantly lower in patients with IMTL (P = 0.000) than in those with HCC but not IHCC (P = 0.558) or MLC (P = 0.514). In contrast to elevated serum CA19‐9 in patients with HCC/IHCC/MLC, the serum CA19‐9 in IMTL cases was generally normal (vs HCC P = 0.008; vs IHCC P = 0.000; vs MLC P = 0.022). In nine IMTL patients, the tumor appeared as a hypoechogenic solid mass on the ultrasonography. In contrast, most patients with HCC, IHCC, or MLC showed hybrid echo. In contrast computed tomography and magnetic resonance imaging, the lesion of IMTL and MLC appeared as peripheral enhancement. Conclusion Lab tests, imaging features, and patient history are helpful in the differential diagnosis of IMTL from HCC/IHCC/MLC. Surgical resection is curative for IMTL.